Risks and Outcomes of Spinal Deformity Surgery in Chiari Malformation with Syringomyelia versus Adolescent Idiopathic Scoliosis - Godzik, Jakub (Spine J, 2015)
BACKGROUND CONTEXT: Chiari Malformation, Type 1, with syringomyelia (CIM+SM) is often associated with spinal deformity. The safety of scoliosis surgery this population is controversial, and has never been directly compared with adolescent idiopathic scoliosis (AIS). Purpose: Compare the safety and subjective outcomes of spinal deformity surgery between patients with Chiari Malformation I associated scoliosis and a matched Adolescent Idiopathic Scoliosis cohort. STUDY DESIGN: Retrospective matched cohort analysis PATIENT SAMPLE: Patients with CIM+SM and treated with spinal fusion for spinal deformity were identified in the surgical records of a single institution and were matched, 1:1, with AIS patients undergoing spinal fusion at the same institution. OUTCOME MEASURES: Neurological monitoring data quality and integrity, radiographic parameters, Scoliosis Research Society-22 Scores. METHODS: A clinical database was reviewed for patients undergoing spinal reconstruction for CIM+SM associated spinal deformity at our institution from 2000 to 2012. Thirty-six CIM+SM patients were identified and matched to an AIS cohort (1:1) based on age, gender, major curve magnitude, fusion length, and revision status. Demographics, deformity morphology, surgical details, neuromonitoring data, and pre- and postoperative SRS-22 scores were recorded at a minimum 2-year followup. Changes in SRS-22 scores were compared within and between groups. Complications and neurological monitoring data issues were compared between groups. RESULTS: Mean age was 14.5±5 years (CIM+SM: 14.6±5; AIS: 14.4±5), and 42% of patients were male. Preoperative mean major coronal Cobb measured 58°±25 vs. 57°±17 (p=0.84) with mean kyphosis 52°±17 vs. 41°±20 (p=0.018). An average of 10.4±2.6 vertebral levels were fused (10.4±2.8 vs. 10.4±2.3, p=0.928). No differences existed in surgical approach (p=0.336), estimated blood loss (680mL±720 vs. 660±310, p=0.845), or duration of surgery (6.0 hours ±2.2 vs. 5.6 ± 2, p=0.434). Complication rate was comparable between the two groups (33% vs. 14%, p=0.052). CIM+SM experienced more neurological complications (11% vs. 0%, p=0.04) and neuromonitoring difficulties (28% vs. 3%, p=0.007) than the AIS cohort. Mean curve correction was comparable at 2 years (58% CIM+SM vs. 64% AIS, p=0.2). At follow-up, both CIM+SM and AIS groups demonstrated improved cumulative SRS-22 outcome subscores (CIM+SM: +0.4, p=0.027; AIS: +0.3, p<0.001). No difference in outcome subscores existed between CIM+SM and AIS groups. CONCLUSIONS: While CIM+SM patients undergoing spine reconstruction can expect similar deformity corrections and outcomes scores to AIS patients, they also experience higher rates of neuromonitoring difficulties and neurological complications related to surgery. Surgeons should be prepared for these difficulties, particularly in children with larger syrinx size.